A case of a duplicated superficial branch of radial nerve and a two-bellied brachioradialis muscle presenting a potential entrapment syndrome - Herma, Tomas; Baca, Vaclav; Yershov, Danylo; Kachlik, David (Surgical and radiologic anatomy, 2017)
We have found an interesting coincidental variation of the superficial branch of the radial nerve and the brachioradialis muscle in a male cadaver. The superficial branch of the radial nerve was duplicated with one branch taking an aberrant course between two bellies of the brachioradialis muscle. The variant brachioradialis muscle featured two muscle bellies, a superficial one and a deep one, with one common origin and one common insertional tendon. The accessory nerve branch was impinged by two blood vessels and pierced through muscle bundles connecting two bellies of the brachioradialis muscle. The knowledge of this neuromuscular variant is of clinical relevance for the differential diagnosis of pain and paresthesia on the dorsoradial aspect of the hand and for the surgical management of the Wartenberg's syndrome.
Keywords: kosterní svaly; diferenciální diagnóza; Anatomic Variation; Nerve Compression Syndromes; Entrapment; Tendons; ruka; anatomická variace; lidé; Muscle, Skeletal; šlachy; Diagnosis, Differential; Two-bellied brachioradialis muscle; mrtvola; Wartenberg’s syndrome; úžinové syndromy; Male; Aged; Cadaver; Paresthesia; senioři; mužské pohlaví; Radial Nerve; Hand; parestezie; nervus radialis; Radial nerve; Humans